Relación genómica entre citotipos diploides de Paspalum simplex y P. procurrens (Poaceae, Paniceae) - Espinoza, Francisco; Quarin, Camilo Luis (Instituto de Botánica Darwinion, 1998)
Interspecific Crossing was conducted between diploid cytotypes of two Paspalum species o f the subgenus Anachyris in order to investígate their genomic relatíonship and to evalúate the possibilities of gene exchange between these species as a tool for their genetic improvement. Paspalum simplex was the female parent. The Ft hybrids showed stoloniferous growth habit which is characteristíc of the male parent, P. procurrens. Regular meiotic behavior in the F, hybrids demonstrated that both species have significant homology in their genomes. Embryological studies and seed production analysis under self and cross-pollinated conditions demonstrated that the hybrids, like their parents, are sexual and selfsterile but cross-compatible. Both, the high level of crossabitity o f the parents and the degree of fertility observed in hybrids and in backcross progenies, indicated the feasibility of gene exchange between these species. Morphologically, P. simplex and P. procurrens are easily recognized as different species. Notwithstanding, the high crossability and the high level o f fertility observed in hybrids and backcrossed progenies contrast with the lack of intermedíate forms observed in herbaria and during field trips. Diploid cytotypes of both species seem to be restricted to western arcas of the phytogeographic Chaco province, from Bolivia to Argentina. However, divergent evolution likely occurred in correlation with latitude and specific soil requirements. Diploid P. simplex was found in the southwestem Chaco province on clayey soil while P. procurrens was collected in the northwest o f the province, growing on sandy soil.
Keywords: Híbridos interespecíficos; Paspalum simplex; Paspalum procurrens; Paniceae; Interspecific hybrids; Paspalum simplex; Paspalum procurrens; Paniceae; Poaceae